IMPLICATURE USED AT THE POLITICS NEWS OF THE JAKARTA POST, JAWA POS NEWSPAPER AND ITS PEDAGOGIC IMPLICATIONS - Widya Caterine Perdhani (Erudio Journal of Educational Innovation, 2013)
Implicature in a broad sense requires what a speaker means is determined by the speaker's intentions in a given context. Many people use implicature in a certain fields for example in politics. In addition, politicians also use implicature in any situation to win his or her idea. Therefore they try to imply a bad association into a good one in many types and meanings of implicature. In This Journal , The writer discuss about the Implicature Politics and It’s Pedagogics Implication that found in Jakarta Post and Jawa Pos. Key Words : Implicature, Speech act , Maxims